2020
DOI: 10.1136/emermed-2020-209797
|View full text |Cite
|
Sign up to set email alerts
|

Strategic planning and response to COVID-19 in a London emergency department

Abstract: For many of us in emergency medicine, rising to the challenge of the COVID-19 crisis will be the single most exciting and challenging episode of our careers. Lessons have been learnt on how to make quick and effective changes without being hindered by the normal restraints of bureaucracy. Changes that would normally have taken months to years to implement have been successfully introduced over a period of several weeks. Although we have managed these changes largely by command and control, compassionate leader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 0 publications
0
12
0
2
Order By: Relevance
“…After patients who visited emergency medical centers were confirmed with the infection, 2 regional emergency medical centers and r local emergency medical centers were temporarily shut down. [ 3 ] As COVID-19 accompanied several symptoms, it was difficult to differentiate patients with suspected infection, and there were no separate zones established to isolate patients besides a few existing isolation beds. Furthermore, because we could not accept new patients with suspected infection until test results of the patients already in the isolation beds were confirmed, the bed turnover rate also decreased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After patients who visited emergency medical centers were confirmed with the infection, 2 regional emergency medical centers and r local emergency medical centers were temporarily shut down. [ 3 ] As COVID-19 accompanied several symptoms, it was difficult to differentiate patients with suspected infection, and there were no separate zones established to isolate patients besides a few existing isolation beds. Furthermore, because we could not accept new patients with suspected infection until test results of the patients already in the isolation beds were confirmed, the bed turnover rate also decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Patients suspected of having the infection were treated in the isolation zone, whereas those who are not suspected were instructed to enter the clean zone. Whitwell et al [ 3 ] documented the separation of isolation and clean zones in places with wide space available for patient care, and Chung et al [ 4 ] reported cases in which the area outside the ED was utilized to provide care for suspected patients or perform X-ray and cardiopulmonary resuscitation. Although we were able to isolate multiple patients as a cohort in the isolation zone, the COVID-19 screening test was time-consuming, and proactively isolating suspected patients as a cohort was associated with a risk of spreading the infection among these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The gap identified from the review highlighted a need to focus on reviewing healthcare workers about who, how, and why they conduct strategy in hospitals. In light of the coronavirus disease 2019 (COVID-19) pandemic becoming the major disruptor for healthcare and hospital sites in particular (Bowman et al, 2020;Pellino et al, 2020;Staib & Small, 2020;Steier & Moxham, 2020;Whitwell et al, 2020;Zeng et al, 2020), it would be of benefit to examine the literature to see how hospitals conduct strategy, to inform future research in the field.…”
Section: Strategy In Different Organisational Sectorsmentioning
confidence: 99%
“…However, as we enter a new decade, hospitals are already struggling to cope with increasing service demands and activity. They need to become more responsive to changes in their environment and demonstrate more effective use of available resources (Bowman et al, 2020;Staib & Small, 2020;Steier & Moxham, 2020;Whitwell et al, 2020;Zeng et al, 2020). On an international level, growing numbers of hospitals within the public sector are empowered to develop their own strategic, financial and clinical directions, so they must be ready to redefine roles and set clear goals for service delivery (Saltman et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays the afore mentioned propositions require more intense attention, since our experience from CoViD-19 pandemic, demonstrated globally that the current organisation of public health sector poses obstacles for the management and must be reorganized with the application of horizontal procedures which should overcome the slow bureaucratic rhythms and the conventional hierarchical system structure (Whitwell, Maynard, Barry, Cowling, & Taraet, 2020). An important factor towards success, by implementing lean management or other organisational changes, is the existence of efficient and competent managers who promote collective work (Kotter, 1996;Diefenbach, 2013;Lytras, 2016: p. 40) while at the same time, we must bear in mind that professionally defined strategies, "resting upon clearly defined laws, rules, and principles, as a foundation" and under "complete written instructions" (Taylor, 2003: pp.…”
Section: Theoretical Framework-setting the "Lean" Scenementioning
confidence: 99%